Military Expenditure : International Comparison of Trends - Hewitt, Daniel (IMF Working Papers; Working Paper ;, 1991)
This paper analyzes trends in world military expenditure by examining the shares of different country groups and the ratio to GDP of individual nations. The coverage is military expenditures in 125 countries from 1972 to 1988. The study also compares military expenditures as a proportion of central government expenditures; analyzes the budgetary trade-off between military, social, and development expenditures; and discusses the impact of military expenditures on economic development.